Overview of North American Isolates of Chronic Wasting Disease Used for Strain Research - W. David Walter; Allen Herbst; Chia-Hua Lue; Jason C. Bartz; M. Camille Hopkins (Pathogens)
Chronic Wasting Disease (CWD) is a prion disease that affects Cervidae species, and is the only known prion disease transmitted among wildlife species. The key pathological feature is the conversion of the normal prion protein (PrPC) misfolding into abnormal forms (PrPSc), triggering the onset of CWD infections. The misfolding can generate distinct PrPSc conformations (strains) giving rise to diverse disease phenotypes encompassing pathology, incubation period, and clinical signs. These phenotypes operationally define distinct prion strains, a pivotal element in monitoring CWD spread and zoonotic potential—a complex endeavor compounded by defining and tracking CWD strains. This review pursues a tripartite objective: 1. to address the intricate challenges inherent in ongoing CWD strain classification; 2. to provide an overview of the known CWD-infected isolates, the strains they represent and their passage history; and 3. to describe the spatial diversity of CWD strains in North America, enriching our understanding of CWD strain dynamics. By delving into these dimensions, this review sheds light on the intricate interplay among polymorphisms, biochemical properties, and clinical expressions of CWD. This endeavor aims to elevate the trajectory of CWD research, advancing our insight into prion disease.